Haiti : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper reviews economic developments in Haiti during 1990-94. In the public finances, the current account of the nonfinancial public sector (before grants) shifted from balance in 1991 to a deficit of 3.8 percent of GDP in 1994. With the lack of foreign financing, capital investment fell to low levels over the period, and the overall deficit (before grants) declined from 4.5 percent of GDP to 4.2 percent of GDP; the deficit was financed mainly by recourse to central bank credit and the accumulation of arrears.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet